Application of Electric Arc Furnace Oxidizing Slag for Environmental Load Reduction - Kim, Sang-Woo; Lee, Yong-Jun; Lee, Jung-Yoon; Kim, Kil-Hee (Asian Journal of Chemistry, 2014)
This paper presents the applicability of electric arc furnace (EAF) oxidizing slag in construction to reduce the environmental load. This study illustrates the properties and characteristics of EAF oxidizing slag as well as explains the advantages obtained from using EAF oxidizing slag as an aggregate for structural concrete. Furthermore, in order to expand the recyclable range of EAF oxidizing slag aggregates, its applicability to concrete for prestressed high-strength concrete (PHC) piles was experimentally estimated. The experimental results show that applying EAF oxidizing slag aggregates to PHC piles enhances the compressive strength, saves energy, lowers carbon dioxide emissions, reduces the amount of cement used and helps to cut costs.